2011
DOI: 10.1037/a0020519
|View full text |Cite
|
Sign up to set email alerts
|

Experimental renewal in human participants.

Abstract: Two experiments with human participants are presented that differentiate renewal from other behavioral effects that can produce a response after extinction. Participants played a video game and learned to suppress their behavior when sensor stimuli predicted an attack. Contexts (A, B, & C) were provided by fictitious galaxies where the game play took place. In Experiment 1, participants who received conditioning in A, extinction in B, and testing in A showed some context specificity of conditioning during exti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 58 publications
8
74
1
1
Order By: Relevance
“…The blue armrest was covered with a fine-grain plastic material. Display backgrounds (Cook et al, 2010;Nelson et al, 2011) and lighting changes (Van Gucht, Vansteenwegen, Beckers, & Van den Bergh, 2008;Vansteenwegen et al, 2005) have been shown to be effective context manipulations in single-room procedures.…”
Section: Contextsmentioning
confidence: 99%
“…The blue armrest was covered with a fine-grain plastic material. Display backgrounds (Cook et al, 2010;Nelson et al, 2011) and lighting changes (Van Gucht, Vansteenwegen, Beckers, & Van den Bergh, 2008;Vansteenwegen et al, 2005) have been shown to be effective context manipulations in single-room procedures.…”
Section: Contextsmentioning
confidence: 99%
“…Participants were initially screened to remove those who failed to learn the basic task during the first phase. Participants for whom suppression ratios on two out of the last three trials of the first phase of conditioning were not lower than the first trial were to be excluded (see also Nelson et al 2011b). In previous reports using this method (e.g., Nelson et al 2011aNelson et al , 2012 we excluded participants who had low pre-CS responding (average <5) as that procedure was successful in eliminating the occasional pre-CS response rate of zero for which calculation of a suppression ratio would be uninterpretable.…”
Section: Discussionmentioning
confidence: 99%
“…The present experiment used the same parameters as were used in the first two attention-arousing phases of that study. The design is shown in Table 1 There is considerable evidence that context changes with the method are easily discernible Sanjuan 2006, 2008;Nelson et al 2011b;Nelson et al 2012Nelson et al , 2013), nevertheless we included four additional groups to ensure that is the case with the present samples and parameters. All four of these groups received conditioning and extinction of X in the same way as did Group With Extinction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations